5‐diphenylacetamido‐indirubin‐3′‐oxime as a novel mitochondria‐targeting agent with anti‐leukemic activities. Issue 5 (18th March 2015) - Song, Ju Han; Lee, Jung‐Eun; Cho, Kyung‐Min; Park, Su‐Ho; Kim, Hyeoung‐Joon; Kim, Yong‐Chul; Kim, Tae Sung
Abstract : Current treatment for leukemia largely depends on chemotherapy. Despite the progress in treatment efficacy of chemotherapy, a poor outcome consequent upon chemoresistance against conventional anti‐cancer drugs still remains to be solved. In this study, we report 5‐diphenylacetamido‐indirubin‐3′‐oxime (LDD398) as a novel mitochondria‐targeting anti‐leukemic agent, which is a derivative of indirubin used in traditional medicine. Treatment with LDD398 resulted in caspase activation, cell death, and growth arrest at G2/M phases in leukemia cells. Interestingly, LDD398 quickly collapsed mitochondrial membrane potential (MMP) within 1 h, accompanied by cytochrome c release into cytosol and severe depletion of cellular ATP. However, the LDD398‐induced cellular events was significantly mitigated by blockage of mitochondrial permeability transition pore (MPTP) opening with chemical and genetic modifications, strongly supporting that LDD398 executes its anti‐leukemic activity via an inappropriate opening of MPTP and a consequent depletion of ATP. The most meaningful finding was the prominent effectiveness of LDD398 on primary leukemia cells and also on malignant leukemia cells resistant to anticancer drugs. Our results demonstrate that, among a series of indirubin derivatives, LDD398 induces leukemia cell death via a different mode from indirubin or conventional chemotherapeutics, and can be employed as a potent anti‐cancer agent in the treatment for newly diagnosed and relapsed leukemia. © 2015 Wiley Periodicals, Inc.